A review of the genus Apristurus (Chondrichthyes: Carcharhiniformes: Scyliorhinidae) from Taiwanese waters - Nakaya, Kazuhiro; Kawauchi, Junro (Zootaxa, 2013)
Sharks of the genus Apristurus from Taiwanese waters are reviewed for the first time, and incorrect scientific names and wrong taxonomic information given in the literature are corrected. After extensive examination of specimens deposited in various museums, universities and fisheries institutions in Taiwan, Japan and China, the following five species are recognized from Taiwanese waters: Apristurus herklotsi (Fowler, 1934), A. longicephalus Nakaya, 1975, A. gibbosus Meng, Chu & Li, 1985, A. macrostomus Chu, Meng & Li, 1985, and A. platyrhynchus (Tanaka, 1909). Apristurus herklotsi, A. longicephalus, A. gibbosus and A. macrostomus are reported from Taiwanese waters for the first time, and the presence of A. platyrhynchus is formally recognized based on a single voucher specimen. Each species is fully described, and a key to the species of Apristurus in Taiwanese waters is provided. Morphological and biological information of each species is also provided.